First-line treatment of camrelizumab combined with chemotherapy in advanced gastroenteropancreatic neuroendocrine carcinoma: Study protocol for a prospective, multicenter, phase II study - Li, Xiaofen; Ma, Qing; Chang, Chen; Li, Hao; Cao, Dan (Frontiers in Oncology, 2022)
Background: Gastroenteropancreatic neuroendocrine carcinoma (GEP-NEC) is a group of rare but highly aggressive malignancies. The standard chemotherapy regimens composed of etoposide and cisplatin /carboplatin (EP/ EC) are of limited efficacy. This prospective, multicenter, phase II study is conducted to explore the effectiveness and safety of first-line anti-PD-1 antibody (camrelizumab) combined with chemotherapy in advanced GEP-NEC patients. Methods: Patients with unresectable or metastatic GEP-NEC will receive camrelizumab combined with standard first-line chemotherapy every three weeks (camrelizumab 200 mg, administered intravenously on day 1; etoposide 100 mg/m2, administered intravenously on days 1-3; cisplatin 75 mg/ m2, administered intravenously on day 1 or carboplatin area under the curve 5 mg/mL per min, administered intravenously on day 1). All patients were naïve to systemic therapy in the advanced setting. The primary end point is 6-month progression-free survival (PFS) rate. The secondary end points are objective response rate, PFS, overall survival and adverse reactions. Discussion: This is the first study to investigate therapeutic potential of camrelizumab plus chemotherapy for advanced GEP-NEC. It is expected that this trial will propose a new and effective treatment strategy for GEP-NEC in first-line setting. Trial Registration: This trial is registered at Chinese Clinical Trial Registry (ChiCTR2100047314). Date of Registration: June 12, 2021.